PENERAPAN TEHNIK ABCD PADA POSYANDU LANSIA DALAM PEMENUHAN KEBUTUHAN FISIOLOGIS LANSIA DI POSYANDU SALAK 94 GUMUKMAS - Maulana, Puji; Aulia, Farissa; Azizah, Putri; Rumayanti, Ratna; Fauzi, Muhammad Fikri (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
Posyandu for the Elderly is an integrated community-based health service designed to ensure that older adults receive appropriate and accessible healthcare. This study aims to explore the implementation of the Asset-Based Community Development (ABCD) method within the Elderly Posyandu program in Karanganyar Hamlet, Gumukmas District. The research focuses on fulfilling the physiological needs of the elderly, particularly in terms of nutritional and health-related aspects. The ABCD method emphasizes the mobilization of local assets and community potential, allowing older adults to take an active role in maintaining their own health. The findings indicate that the Elderly Posyandu program has effectively enhanced the elderly’s awareness of the importance of health, mainly through early detection of common diseases such as hypertension and diabetes, as well as counseling on healthy dietary practices. Posyandu cadres regularly conduct health assessments—including measurements of height, weight, and blood pressure—and provide education on the balanced nutritional intake required by older adults.